Minimizing Capacitance Value of Interleaved Power Factor Corrected Boost Converter for Battery Charger in Electric Vehicles - Turksoy, Omer; Yilmaz, Unal; Teke, Ahmet (Elektronika ir Elektrotechnika, 2019)
A dynamic voltage compensator (DVC) technique is presented for the minimizing of the capacitance value of the interleaved power factor corrected (PFC) boost converter for the battery charger in electric vehicles. This technique is based on eliminating the ripple on the capacitor by creating a voltage in the opposite direction as well as the amount of ripple on the capacitor. With the proposed method, the capacitance value is reduced by approximately five times. Reducing the size of the capacitor also provides the use of film-capacitors with a longer life. The other contribution of this study is designing a faster and more stable fully-digital control system, instead of the commonly used analogue controller of interleaved PFC boost converter. A 3.3 kW interleaved PFC boost converter is designed to verify the effect of the designed dynamic voltage compensator and digital controller.